If Voting Is So Important, Why Aren't Fair, Open, Verifiable Elections Important? - SWANSON, DAVID (Humanist)
The author discusses impossibility of not encountering demand to vote in U.S. society and mentions reforming the U.S. system of elections. Topics discussed include book "The Hidden History of the War on Voting" by Thom Hartmann, cases of documentation of racism and disinformation campaigns, and peace talk sabotaged by former president Richard Nixon.